Obtenção e caracterização de compósitos caulinita/pigmento e aplicação em artefatos de borracha - Oliveira, Robinei dos Reis de (2009)
Nowadays in the rubber artifact industries, are used as inorganic pigments such as those classified as organic in large numbers in the industries of rubber, which is designed to provide various kinds of colors by mixing these pigments which follow the fashion trend. However, when these pigments are exposed to high temperatures, such as in the vulcanization process, there can be migration or degradation of the standard tonality of the product. Although the pigment producers offer high thermal resistant products, in practice they do not present a favorable performance in the vulcanization process. In this work, the DMSO was intercalated in the kaolinite and used as a spacer agent of its laminules trying to facilitate the intercalation of the red and yellow pigments. In the pigment preparation for intercalation octan-1-ol was used to dissolve and then to the kaolinite. The mixture was left under reflux in the silicon bath for 7 days at 70ºC. The pigments were characterized by the diffraction of X-rays, infrared and UV-VIS spectroscopy, thermal analysis (TG/DTG), as well as tests in the process of rubber vulcanization, before and after intercalation of them, with the observation of the comparatives in the visual aspect whose objective was to verify the pigment degradation after vulcanization at around 160ºC. The results showed that the plate with the vulcanized composite pigments / kaolinite obtained a better result compared to the plate with pure pigment. It is noteworthy that no deviation has been observed in tone plate with the vulcanized composite. KEY WORDS: Intercalation; pigment; temperature.